Analisis Faktor-Faktor yang Memengaruhi Dividend Payout Ratio pada Perusahaan Sektor Industri yang Terdaftar di Bursa Efek Indonesia - Sunaryo Sunaryo (Bina Nusantara University, 2014)
The primary objective of this research is to learn the effect among return on assets (ROA), current ratio (CR), debt to equity ratio (DER), debt to total assets (DTA), and net income after tax (NIAT) with dividend payout ratio (DPR), either partially or simultaneously. Research used qualitative method with secondary data collected by purposive sampling from industrial companies sector listed in IDX and preceding journals of scientific articles. Research used simple regression to test the hypothesis simultaneously with F test and t test for testing the partial hypothesis. Results of this research describe that return on assets (ROA) and net income aftar tax (NIAT) have significant effects to dividend payout ratio, but current ratio (CR), debt to equity ratio (DER), and debt to total assets do not have significant effects to dividend payout ratio. It is recommended to further research that the topic of this reseach can be continued using merchandising and distribution company groups, or service company groups either general or special, like: hotels, insurances, hospitals, and banks.